Stinky Cheese Vacation - Stilton, Geronimo (New York Scholastic Inc., 2014)
Geronimo Stilton #57: The Stinky Cheese Vacation is an enjoyable read for young readers between 6 and 10 years of age. The stories in the entire Geronimo Stilton series by Elisabetta Dami are fast-paced and fun. In addition, the books have been made colourful through vibrant artwork and have been presented in a unique format and with funky font that makes reading all the more interesting for the little ones. Geronimo Stilton, a little mouse journalist, is in the process of finishing up with all his chores one fine evening. This is when he opens the letter that he had received from his Uncle Stingysnout. In the letter, Geronimo's uncle gives him an urgent message. The letter tells him that Stingysnout needs to see his nephew as soon as possible, if possible immediately. It makes Geronimo happy to think that he will be seeing his uncle again and so, without wasting any time, the small mouse heads straight to Penny Pincher Castle. But what does little Geronimo find? Instead of spending a pleasurable vacation, his old uncle Stingysnout has invited him to put him to some boring work. It is turning out to be a stinky vacation for Geronimo. Geronimo Stilton #57: The Stinky Cheese Vacation has been published by Scholastic Incorporation in 2014 and it is available in paperback. Key Features: Geronimo Stilton #57: The Stinky Cheese Vacation is a part of the extremely popular Geronimo Stilton series that was originally published in Italian. This series has been specifically written by the author for children between 6 and 10 years of age.
Keywords: Children Fiction